(untitled) - Gezon, Lisa L. (New York, N.Y., 2012)
This new magazine style text for the Introduction to Cultural Anthropology course offers solid scholarly content and an engaging design that will captivate your students. Through memorable eye-catching pedagogical features, students develop a better understanding of the material and will retain a greater amount of course concepts. This book presents cultural anthropology in a way that is both captivating and relevant to today’s student at a price that they prefer.
Keywords: Anthropology,Văn hoá,Nhân học,Culture